ANALISIS PENGARUH ANGGARAN BERBASIS KINERJA TERHADAP KINERJA MANAJERIAL APARATUR PEMERINTAHAN (Study Empiris pada Badan Pencarian dan Pertolongan) - J.R. Patiruhu; Stenley J. Ferdinandus; Welmin Marlo Komul (Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2018)
This study aims to analyze the influence of budgetary participation on the managerial performance of the apparatus, the influence of budgetary evaluation on managerial performance of the apparatus, the influence of budget target clarity on the managerial performance of the apparatus, the influence of budget planning on the managerial performance of the apparatus and the influence of budgetary usage on apparatus managerial performance at Search and Relief Agency (BASARNAS).This research is empirical research, with sampling technique used is purposive sampling with criterion of respondent in this research is employee who perform function of accountancy / financial administration at Search and Relief Agency (BASARNAS), covering Head of Agency as official of budget user, head head of the unit as the authorized user of the budget / power of the goods user and the head of the field and part as the commitment maker (PPK). Data obtained through questionnaires distributed to the selected sample respondents. The analysis used was multiple regression analysis with the least squares equation and hypothesis test using t-statistic to test the partial regression coefficient and F-statistic to influence influence together with 5% confidence level.The result of the study shows that budget participation has a significant positive effect on managerial performance. Budget evaluation has positive but insignificant effect on managerial performance. The clarity of budget targets has a significant positive effect on managerial performance. Budget planning has a significant positive effect on managerial performance and Budget use has a significant positive effect on managerial performance. In addition, the variability of dependent variables that can be explained by the variability of independent variables is 94% while the remaining 6% is explained by other variables not included in the regression model.Keywords: Budgeting, Budget Evaluation, Budget Objective Clarity, Budget Planning, Budget Use, Managerial Performance